KUALITAS SENSORY RENDANG DAGING SAPI PADA BEBERAPA RUMAH MAKAN PADANG DI KOTA AMBON - Yuliana Apalem; Nafly Comilo Tiven; Isye Jean Liur (MARSEGU : Jurnal Sains dan Teknologi, 2026)
This study aims to determine the sensory quality of beef rendang in several Padang restaurants in Ambon City. The sensory quality test of beef rendang used 25 untrained panelists, with the observed sensory parameters of beef rendang, namely color, tenderness, and taste. The data obtained were analyzed using a Complete Random Design (RAL) with 5 treatments of Padang restaurants, with the initials RPS, RTG, RTR, RSL, and RAS. The differences between treatments were further tested with the Duncan Test. Based on the results and discussions, it can be concluded that each Padang restaurant has different sensory and chemical qualities of rendang.